Longing Itineraries: Building the Translocal Community - López Angel, Gustavo (2017)
Migration has reshaped social practices, the sense of belonging has been rethought, and the membership is renegotiated and contended; this is why strategies for their sustainability have been generated. The translocal community operates through multilocated relationships that reveal the ways in which migrants are adapting to the new demands of the community. We emphasize the emotional impulse of nostalgia as one of the vehicles of sustainability for the community. The community is redefined and understood in a set of socio-cultural relationships its members generate, and where the locality is not central, but the connection. A new dimension of the social community space is not just the community gathered in a specific place, but also that agreements, commitments, and acknowledgments are exhibited and settled in the cyberspace; this cyberspace gives cohesion and brings a dynamic element to preserve the community, despite the fact that it is even less concrete than the spatial notion of territory. Facebook, YouTube and a blog are the web platforms of the virtual space where "neighbors, compatriots and citizens" (categories of ascription from the migration) get together, where there is a reproduction of social practices (even the most ancient and fundamental ones), to give a new dimension to a translocal, multilocated and ciberlocated community.